ANALISA REKAYASA SIFAT MEKANIK BAJA AISI 4140 DENGAN VARIASI SUHU TEMPERING UNTUK MENINGKATKAN KEULETAN DAN KEKERASAN MATERIAL - Shultoni Mahardika (universitas teuku umar, 2020)
Steel is a type of material that is widely used as a main material in the manufacture of various kinds of industrial and automatic machinery spare parts. Some mechanical properties of steel that are often used in design are hardness, ductility and toughness. Often in a design, we have difficulty getting steel with mechanical properties that are appropriate with the design. For this reason, engineering carried out mechanical properties engineering, to obtain steel in accordance with design calculations. AISI 4140 steel is a medium alloy steel. This steel is often used for industrial and automotive machinery parts. This research engineered the mechanical properties of the steel, namely the hardness and ductility of the material. The process is carried out by conducting steel hardening at 850 °C followed by rapid cooling with water media. After that, tempering at temperatures of 300 ᵒC, 400ᵒC and 500ᵒC by cooling together with the furnace. The result is hardness and tensile strength of the material has increased, when compared with untreated material. This method is effectively used to obtain mechanical strength values in accordance with technical planning calculations. . Keywords: Tempering, AISI 4140, Mechanical Properties Engineering